Modernisation du secteur public et transformation du pouvoir d’agir des salariés. Le cas de Gaz de Bordeaux - Maël Dif-Pradalier (La Nouvelle Revue du Travail, 2012)
The article examines the reconfiguration of work in a public sector company that is in the process of being transformed and examines the conditions that may or may not be promoting the empowerment of worker collectives and/or professional associations. By comparing two different problem resolution approaches in two different departments, it shows that even when a union manages to voice some of these problems, workers are still kept from designing their work organisation and remain subject to work criteria that they have no possibility of discussing. The article concludes by arguing that employees’ empowerment can only be developed if they are no longer viewed solely as victims of the organisation of work, in its construction as a prerogative for senior management alone. Finally, it calls for a sociological approach including tools and methodologies developed by activity clinics to improve understanding of what is at stake at the worker collective level.